for this we can use the Pythagorean theorem. which is a^2 + b^2 = c^2. Variables a and b can be replaced with the legs of a triangle, and the hypotenuse is c. So using x for the unknown leg of the triangle, we have squarerootof13^2 + x^2 = 7^2. Now we can cancel out the square root by raising it to the second power, and 7 to the second power is 49. Now we have 13 + x^2 = 49. Subtracting 13 from both sides to cancel it out, we can now get x^2 = 36. Now we square root both sides to cancel the exponent. the square root of 36 is 6. Which is your answer.